HEDGING CRYPTOCURRENCY SEBAGAI ALTERNATIF DALAM INVESTASI - Meigia Nidya Sari (Jurnal Bina Akuntansi, 2023)
ABSTRACT This research analyzes cryptocurrency as a hedging investment that is attractive to investors with their hopes. However, cryptocurrency is still much more risky than equity or commodities, Investors are attracted by the dynamics of cryptocurrency which shows that it is very similar to gold and forex investments. Variables in this research (1) Independent Variable is JCI (Rupiah) which is the Combined Stock Price Index. Overview of stock price movements in Indonesia as a whole. (2) Dependent variable is Bitcoin (Rupiah) which is a cryptocurrency. This type of research is quantitative and data processing to produce a hypothesis in this research using the Eviews 11 application. The result of the research is that Bitcoin has hedging capabilities against the stock market in normal conditions, the first hypothesis is accepted. Bitcoin has no hedging ability against the stock market in abnormal economic conditions. The second hypothesis is rejected Keywords: Cryptocurrency, Bitcoin, Hedging, Investment Return ABSTRAK Penelitian ini menganalisis cryptocurrency sebagai hedging dalam investasi yang menarik bagi investor dengan harapannya. “Saat ini cryptocurrency dapat dilihat lebih berisiko daripada ekuitas dan Investor tertarik dengan dinamika cryptocurrency yang menunjukkan bahwa ia sangat mirip dengan emas dan investai forex.” Variabel yang diteliti, (1) varibal independen IHSG (Rupiah) yaitu Indeks Harga Saham Gabungan, hal ini gambaran pergerakan harga saham di Indonesia secara keseluruhan, (2) variabel dependen adalah Bitcoin (Rupiah) yaitu Mata uang kripto yang merupakan cryptocurrency. “Jenis penelitian ini adalah kuantitatif dan olah data untuk menghasilan hipotesis dalam penelitian ini menggunkanan aplikasi Eviews 11.” Hasil penelitian yaitu Bitcoin memiliki kapabilitas hedging terhadap pasar saham pada keadaan normal, Hipotesis pertama diterima. Bitcoin tidak memiliki kemampuan lindung nilai terhadap pasar saham dalam kondisi ekonomi yang tidak normal. Hipotesis kedua ditolak Kata Kunci: Crytocurrency, Bitcoin, Hedging, Return Investasi